Compreensões sobre plantões de atendimento psicológico: em foco o Plantão Psicoeducativo - Pestana, Daniel de Olival (2017)
The Psychoeducational Duty Inspired by Psychological Attendance, is a modality of psychological care that has been (im)planted in formal and non-formal education equipment. In these deployments, it has also been constituted as a psychoeducational practice through researches and actions of psychologists engaged in psychology and education. It is understood that, in order to improve the attendance, it is necessary to reflect on it so that improvements can be generated. Thus, this research sought to broaden the knowledge and practice regarding this modality with the objective of identifying how the teachers of a public school perceived the psychoeducational stance based on their experiences with it. For that, a period of intervention was carried out on duty, and then a Reflective Interview (SZYMANSKI, 2002) with two teachers of an EMEF, located on the outskirts of the northern part of the city of São Paulo. The method of investigation and analysis was based on the existential phenomenological orientation, where it was possible to identify the psychoeducational work as listening and looking that promote reflection. Specialized listening and gazing were essential tools in the constitution of reflection and in the invitation to action, as they brought different perspectives of professional action for the teachers. Because it did not depend on a traditional setting, the Duty was kept in transit, happening in the institution's settings. So it was perceived as places, moments and expectations. The places were the environments of the school where the Duty happened and the moments (calls) happened. The need for psychological care at school on other days, in addition to those on duty, generated expectations among the teachers. The Duty was also perceived as legitimation of speech, the testimony, in which the words of the teachers, in the attendances, gained another importance. It is considered that there is a need for specific psychological care (such as the Psychoeducational Duty), in the school context, that allows comprehensive and joint understandings with the teaching staff. The teaching also demonstrated that it needs spaces that promote new reflections on its practice